A Literature Review of Islamic Mediation (As-Sulh) As Mechanism for Settling Marital Dispute among Muslim Couples in Northeastern Nigeria - Muhammad, Adamu Abubakar; Idriss, Ibrahim Dahiru; Ardo, Adam Muhammad; Mohammed, Yakubu Zulaihat (Institut Agama Islam Negeri Padangsidimpuan, 2023)
This research examines the effectiveness of Islamic mediation as-Sulh as a mechanism for settling marital disputes among Muslim couples in Northeastern Nigeria. Islamic mediation as-Sulh is a branch of Islamic law that arbitrates and settles disputes between parties without using a formal court process. In Muslim communities all around north-eastern Nigeria, an alternative dispute resolution (ADR) procedure is regarded as a peaceful and less expensive choice for resolving marital conflicts. This study employs a qualitative research methodology based on a review of the literature and interviews with professionals in Islamic law, mediation, and conflict resolution. The data gathered from the interviews is analyzed using content analysis methods. The findings of the study show that Islamic mediation as-Sulh is an effective mechanism for settling marital disputes among Muslim couples in Northeastern Nigeria. The study's findings imply that Muslim couples in Northeastern Nigeria should use Islamic mediation as-Sulh more frequently as a successful and culturally suitable method of resolving marital conflicts. The study also highlights the importance of further research on this topic in order to better understand the strengths and weaknesses of this form of Alternate Dispute Resolution.